New Cloud Computing-Based Strategy for Coordinating Multi-Robot Systems - Urrea-Onate, E (IGI Global, 2023)
Construction and manufacturing are performed in environments where automation is highly appreciated as it improves security and efficiency. This article proposes a new cloud computing-based strategy for coordinating multi-robot systems aimed to transport and manipulate heavy objects like a beam. The proposed solution is applied to a team of dynamically modeled selectively compliance assembly robot arms (SCARAs) with four degrees-of-freedom (4-DoF), simulated in virtual reality modeling language (VRML) and coordinated by a cloud server. The SCARAs are organized on a leader/follower configuration, so that the leader performs a computed trajectory, constantly reporting its position to the remote server and this, in turn, resends this information to the followers. The SCARAs are modeled using MatLab and they communicate through a transmission control protocol (TCP) with a Python process running in the cloud server to demonstrate the feasibility of incorporating cloud resources in a multi-robot system, testing their performance through simulation. © 2023, IGI Global.